2011
DOI: 10.1097/mnm.0b013e328341a375
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m-hexamethylpropylene amine oxime lung scintigraphy findings in patients with Behçet's disease

Abstract: The degree of pulmonary vascular endothelial damage was represented as increased L/Li ratios and decreased lung clearance rate measured on the Tc-99m-HMPAO lung scan in patients with BD. Our results indicated that determining the T1/2 values and the L/Li ratios on Tc-99m-HMPAO lung imaging should be an objective method to assess subclinical pulmonary damage even in the early stages of BD in the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the pathological correlation of the parenchymal changes has been reported only in a few cases [ 27 , 28 ]. Several studies have investigated the role of lung scintigraphy in patients with BD and suggested that microvascular changes could be shown with scintigraphic techniques even in the early stage of BD [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathological correlation of the parenchymal changes has been reported only in a few cases [ 27 , 28 ]. Several studies have investigated the role of lung scintigraphy in patients with BD and suggested that microvascular changes could be shown with scintigraphic techniques even in the early stage of BD [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%